Electrical injection type‐II (GaIn)As/Ga(AsSb)/(GaIn)As single 'W'‐quantum well laser at 1.2 µm. Issue 22 (11th October 2016) - Fuchs, C.; Berger, C.; Möller, C.; Weseloh, M.; Reinhard, S.; Hader, J.; Moloney, J.V.; Koch, S.W.; Stolz, W.
Abstract : Highly efficient interface‐dominated electrical injection lasers in the near‐infrared regime based on the type‐II band alignment in (GaIn)As/Ga(AsSb)/(GaIn)As single 'W'‐quantum wells are realised. The structure is designed by applying a fully microscopic theory, grown by metal organic vapour phase epitaxy, and characterised using electroluminescence measurements and broad‐area laser studies. A characteristic blue shift of 93 meV/(kA/cm 2 ) with increasing charge carrier density is observed and compared with theoretical investigations. Low threshold current densities of 0.4 kA/cm 2, high differential efficiencies of 66%, optical output powers of 1.4 W per facet, and internal losses of only 1.9 cm −1 are observed at a wavelength of 1164 nm for a cavity length of 930 µm. For a cavity length of 2070 µm, the threshold current density is reduced to 0.1 kA/cm 2 . No indication for type‐I related transitions for current densities up to 4.6 kA/cm 2 is observed.